(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Swami Vivekananda, great patriot saint educationist who dedicated his entire life to the upliftment of humanity, tirelessly working for the spiritual, social, and intellectual advancement of individuals. This philosophical and documentary study employs a purely qualitative approach to examine the contemporary relevance of Swami Vivekananda’s thoughts on emerging educational paradigms such as holistic development, mass education, women’s education and empowerment, peace education, and value education.